2019
DOI: 10.1371/journal.pone.0217084
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of BOLD and GenBank – Their accuracy and reliability for the identification of biological materials

Abstract: Taxonomic identification of biological materials can be achieved through DNA barcoding, where an unknown “barcode” sequence is compared to a reference database. In many disciplines, obtaining accurate taxonomic identifications can be imperative ( e . g ., evolutionary biology, food regulatory compliance, forensics). The Barcode of Life DataSystems (BOLD) and GenBank are the main public repositories of DNA barcode sequences. In this study, an assessment of the accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
174
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(184 citation statements)
references
References 45 publications
7
174
3
Order By: Relevance
“…Working on reference libraries of DNA barcodes of marine organisms (invertebrates and sh taxa), Weigand et al [5] recorded numerous identi cation errors, sequence contamination, incomplete reference (missing trace les or primer information) as inadequate data management. The results of the present study, as supported by other recent studies [2,5,17,28,30,32], reveal that we are still away from possessing decent representative reference libraries for important taxonomic groups. In addition, new DNA barcode data are continuously made available for the already barcoded and additional species from the reference libraries, including additional auditing and annotation processes, altogether helping in closing gap knowledge and purging accumulated erroneous data.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Working on reference libraries of DNA barcodes of marine organisms (invertebrates and sh taxa), Weigand et al [5] recorded numerous identi cation errors, sequence contamination, incomplete reference (missing trace les or primer information) as inadequate data management. The results of the present study, as supported by other recent studies [2,5,17,28,30,32], reveal that we are still away from possessing decent representative reference libraries for important taxonomic groups. In addition, new DNA barcode data are continuously made available for the already barcoded and additional species from the reference libraries, including additional auditing and annotation processes, altogether helping in closing gap knowledge and purging accumulated erroneous data.…”
Section: Discussionsupporting
confidence: 85%
“…The rst indicated that the BINs assignments revealed a sizeable amount of discordances, many are probably related to species misidenti cations or synonyms [28] or the de ciency of the BIN clustering algorithm to correctly discriminate species [30]. The second outcome pointed towards the low power of GenBank results as compared to the BoLD, discrepancies that are already noted in the literature [2,31], characterized by contaminations of the query sequences discordances and misidenti cations. The BoLD and the GenBank data storage systems are highly intermingled.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Correct identification of the specimens present in the reference libraries relies heavily on the taxonomic expertise of the researchers, especially for closely-related, morphologically similar taxa. Since the results obtained in this study depend solely on the BOLD database, a certain level of misidentified sequences reflects the BIN discordance observed (Meiklejohn et al, 2019). We have also identified cases where one species comprised more than one BIN.…”
Section: Biodiversity and Distribution Analysesmentioning
confidence: 89%